Synthesis of glycerol carbonate from the transesterification of dimethyl carbonate with glycerol using DABCO and DABCO-anchored Merrifield resin - Simanjuntak, Fidelis Stefanus Hubertson; Choi, Ji Sik; Lee, Gunuk; Lee, Hye Jeong; Lee, Sang Deuk; Cheong, Minserk; Kim, Hoon Sik; Lee, Hyunjoo (ELSEVIER SCIENCE BV, 2015)
Both DABCO (1,4-diazabicyclo[2.2.2]octane) and Merrifield resin-anchored DABCO ([p-DABCO]Cl), prepared from the reaction of DABCO and Merrifield resin, were found to exhibit high activities for the transesterification of dimethyl carbonate (DMC) with glycerol to produce glycerol carbonate (GLC). FT-IR and NMR spectroscopic results suggest that such a high transesterification activity of DABCO could be attributed to its superior ability to activate glycerol via a strong hydrogen bond formation between a hydroxyl group of glycerol and an amino group of DABCO. Meanwhile, the activation of glycerol by [p-DABCO]Cl proceeds mainly through the hydrogen bond interaction between a hydroxyl group or groups of glycerol and Cl- of [p-DABCO]Cl. The catalytic activity of [p-DABCO]Cl was maintained up to 5 reuses, demonstrating that [p-DABCO]Cl could be used as a recyclable heterogeneous catalyst. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: HETEROGENEOUS CATALYST; HIGHLY EFFICIENT; IONIC LIQUIDS; DIOXIDE